Front Cover. Issue 11 (22nd October 2021) - Frugone, María José; Cole, Theresa L.; López, María Eugenia; Clucas, Gemma; Matos‐Maraví, Pável; Lois, Nicolás A.; Pistorius, Pierre; Bonadonna, Francesco; Trathan, Phil; Polanowski, Andrea; Wienecke, Barbara; Raya‐Rey, Andrea; et al.
Abstract : The cover image relates to the Research Article https://doi.org/10.1111/ddi.13399 "Taxonomy based on limited genomic markers may underestimate species diversity of rockhopper penguins and threaten their conservation" by Frugone et al. Eastern Rockhopper penguins from Marion Island in the sub‐Antarctic region.